Nueva estación del Ferrocarril en la ciudad de Limón - Zamora-Montoya, Daniel (Instituto Tecnológico de Costa Rica., 2012)
During its constructi on and operati on stage, the railroad was the major linchpin in the formati on of the Atlantic Region of Costa Rica and its cultural identi ty. Over twenty years aft er the terminati on of the train service in Costa Rica, we have become conscious again of the advantages of train as a mean of urban transport, so there are nati onal initi ati ves to bring back to operation this service. Limon is not the excepti on, so it is intended to reacti vate the urban train for passengers and as a touristic train service, which end station would be part of the rehabilitati on project of the Pati os del Ferrocarril in this city. Given the need to integrate the functi onality of the main stati on with the cultural characteristi cs of the local people and the historic value of the railroad, and seeking to address the local social needs of recovering trust, hope and pride, it is proposed in this document the architectural soluti on for the New Railway Stati on in the Patios de INCOFER in Limon City.
Proyecto de graduación (Licenciatura en Arquitectura y Urbanismo) Instituto Tecnológico de Costa Rica, Escuela de Arquitectura y Urbanismo, 2012.
Keywords: Costa Rica – Limón; Arquitectura; Ferrocarril; Transporte público; Diseño arquitectónico; Planeamiento urbano; Trenes